2011
DOI: 10.1186/1748-717x-6-47
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic insertion of pelvic tissue expander to prevent radiation enteritis prior to radiotherapy for prostate cancer

Abstract: Radiation enteritis is a significant complication of external beam radiotherapy (EBRT) to the pelvis, particularly in patients having high dose radiotherapy (>80 Gy) and in those with a low pelvic peritoneal reflection allowing loops of small bowel to enter the radiation field. Laparoscopic insertion and subsequent removal of a pelvic tissue expander before and after external beam radiotherapy is a relatively convenient, safe and effective method for displacing loops of bowel out of the pelvis. We report on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The benefit of TEs include easy insertion and removal, lack of adherence to bowel or peritoneum, resistance to degradation by radiation, and being similar in density to human tissue, thereby not altering isodose distribution of radiation ( McKay et al, 2011 ). However, radiation cystitis and proctitis remain common, as the TE does not protect the urinary bladder, ureters, or rectum.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of TEs include easy insertion and removal, lack of adherence to bowel or peritoneum, resistance to degradation by radiation, and being similar in density to human tissue, thereby not altering isodose distribution of radiation ( McKay et al, 2011 ). However, radiation cystitis and proctitis remain common, as the TE does not protect the urinary bladder, ureters, or rectum.…”
Section: Commentmentioning
confidence: 99%
“…In addition, the TE exerts a mass effect on surrounding structures (colon, ureters, urinary bladder, iliac vessels), which may lead to thromboembolism ( Burnett et al, 2000 ), a sensation of heaviness ( Sezeur et al, 1999 ), hydronephrosis and constipation ( Delaloye et al, 1994 ). These risks increase with the size of the TE ( McKay et al, 2011 ).…”
Section: Commentmentioning
confidence: 99%
“…Tissue expanders have shown a reduction of 50% in the risk of chronic intestinal complications in adults 25 and were laparoscopically inserted. 13 Use of pelvic mesh slings has also been reported in children with pelvic malignancies, avoiding radiation-association enteritis in the long-term followup. 16,18 The combination of a tissue expander and a polyglactic acid mesh in a 9-year-old boy relapsing from alveolar rhabdomyosarcoma has allowed 95% of the intestine to be spared from total irradiation.…”
Section: Discussionmentioning
confidence: 97%
“…8 Several surgical or nonsurgical methods have already been described to displace the bowel out of the radiotherapy field with various results in adults. [9][10][11][12][13][14][15] In children, few articles have reported the use of a mesh or a tissue expander to compartmentalize the abdomen and separate it from the pelvis. [16][17][18][19] Herein, we describe the use of the sigmoid colon to function as a hammock by the laparoscopic approach to avoid small bowel irradiation and subsequent consequences.…”
Section: Introductionmentioning
confidence: 99%
“…There is no effective way to displace the small bowel from the pelvis, although a full bladder could help and even a tissue expander was already tested to prevent small bowel from receiving excessive doses of radiation. 16 In addition, others have shown that patient positioning, particularly the Trendelenburg position, may reduce the volume of the small bowel in the PTV. 17,18 It is possible that transection of the umbilical ligaments and urachus during transperitoneal MIRP and detachment of the bladder from the anterior abdominal wall resulted in a higher small-bowel volume around the prostatic bed and PTV.…”
Section: Discussionmentioning
confidence: 99%